(untitled) - Lee, Ruben; Ruben Lee (New York, 1998)
The existence and nature of exchanges used not to be controversial; they were easily identified and characterized. New technology, however, has led to the development of new exchanges and trading systems, posing problems for those concerned with the regulation of trading markets. Ruben Lee examines the question of what an exchange is, using arguments from both financial economics and law, and sets out a view of how exchanges might be regulated
Keywords: Stock exchanges; Futures market